Estructura horizontal de especies comerciales del bosque de colina baja de los fundos Aumento Shiringal Iberia y Nuevo Girardón, distrito del Tapiche, Loreto. 2021 - Macahuachi Paredes, Otoniel (2022)
The horizontal structure of commercial species of the low-hill forest of the Aumento Shiringal Iberia and Nuevo Girardon farms, Tapiche district, Loreto, was determined in 2021. Data from the forest census of commercial species for lumber purposes were evaluated. In the forest of the Aumento Shiringal Iberia farm, 255 trees were registered, comprised in 24 commercial forest species and 16 botanical families; while in the Nuevo Girardon farm, 100 trees were registered, comprised in 8 commercial forest species and six botanical families. The distribution of the number of trees by diameter class of the forest of the Aumento Shiringal Iberia farm is 7,19 trees/ha, while the forest of the Nuevo Girardon farm contains 2,34 trees/ha; in both forests the diameter class of 60 cm to 70 cm contains the highest number of trees. Ecologically, Ciba samauma (Malvaceae) is the most important in the forest of the Aumento Shiringal Iberia farm with an IVI of 39,68%, followed by Maquira coriaceae (31.51%), Capirona decorticans (28.21%), Hura crepitans (26.42%) and Pseudolmedia laevigata (26.16%). In the forest of the Nuevo Girardon farm, Maquira coriaceae (Moraceae) is the ecologically most important species with an IVI of 181,46%, followed by Capirona decorticans (41,05%) and Maquira calophylla (25,11%). The results show no significant difference between the averages of the horizontal structure of the commercial species of the forest of both farms.